Anticholinesterase Compounds from Endemic Prangos uechtritzii. Issue 11 (26th October 2022) - Albayrak, Gokay; Demir, Serdar; Koyu, Halil; Baykan, Sura
Abstract: In this study, the anticholinesterase effects of the extracts and isolated compounds from the roots of endemic Prangos uechtritzii Boiss & Hausskn (Apiaceae) are reported. A novel polyacetylenic compound; (+)‐8‐ O ‐methyloplopantriol A along with two known polyacetylenes; (−)‐panaxynol, (+)‐falcarindiol and fifteen known coumarin derivatives; umbelliferone, 6‐formylumbelliferone, suberosin, 7‐demethylsuberosin, (+)‐ulopterol, tamarin, psoralen, imperatorin, (+)‐oxypeucedanin, (+)‐oxypeucedanin hydrate, (+)‐oxypeucedanin methanolate, (+)‐marmesin, (−)‐prantschimgin, (+)‐decursinol, and (−)‐adicardin were isolated from the hexane (Pu‐HE), chloroform (Pu‐CE), and methanol (Pu‐ME) extracts of P. uechtritzii roots. (−)‐Panaxynol, (+)‐falcarindiol, 6‐formylumbelliferone, (+)‐decursinol, and (−)‐adicardin were obtained from the genus Prangos for the first time. (+)‐8‐ O ‐Methyloplopantriol A inhibited both AChE (IC50 =194.5±5.8 μM) and BChE (IC50 =51.9±2.96 μM) enzymes. (+)‐Falcarindiol, 6‐formylumbelliferone, 7‐demethylsuberosin, tamarin, and imperatorin also exhibited BChE‐specific inhibitory activities (IC50 =27.88‐93.86 μM). (+)‐Falcarindiol (IC50 =27.88±0.91 μM) and imperatorin (IC50 =30.89±1.40 μM) as the most active components could be led compounds to develop new BChE inhibitors with further research against Alzheimer's disease. Abstract :